2014
DOI: 10.1155/2014/793242
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Protection of Diabetic Mice against LethalP. aeruginosaInfection by Bacteriophage

Abstract: The emergence of antibiotic-resistant bacterial strains has become a global crisis and is vulnerable for the exploration of alternative antibacterial therapies. The present study emphasizes the use of bacteriophage for the treatment of multidrug resistant P. aeruginosa. P. aeruginosa was used to induce septicemia in streptozotocin (STZ) induced diabetic and nondiabetic mice by intraperitoneal (i.p.) injection of 3 × 108 CFU, resulting in a fatal bacteremia within 48 hrs. A single i.p. injection of 3 × 109 PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
0
14
0
4
Order By: Relevance
“…The results showed that protection was reduced when the phage treatment was delayed for 4 and 6 hours after a lethal bacterial challenge. 37 Nevertheless, the phage could rescue nondiabetic bacteremic mice even when the treatment was delayed to 20 hours after a lethal bacterial challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that protection was reduced when the phage treatment was delayed for 4 and 6 hours after a lethal bacterial challenge. 37 Nevertheless, the phage could rescue nondiabetic bacteremic mice even when the treatment was delayed to 20 hours after a lethal bacterial challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Phage GNCP treatment of multi-drug-resistant P. aeruginosa infection in diabetic and non-diabetic mice, which caused fatal bacteremia within 2 d, at a 10:1 ratio of phage:bacteria resulted in protection of 90% of diabetic animals and 100% of non-diabetic animals [91]. Bacteriophages were also effective in reducing inflammation in a murine acute infection model of P. aeruginosa [92].…”
Section: Bacteriophage Therapy Of Pseudomonas Aeruginosamentioning
confidence: 99%
“…injection of MDR P. aeruginosa , a single i.p. injection of phages 20 min after bacterial injection increased survival [19]. The authors reported a survival rate of 90% in diabetic and 100% in nondiabetic mice even when treatment started 4 h after bacterial challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment started 6 h after infection resulted in lower survival rates among diabetic mice. Further delay of treatment (12 h) also reduced the effectiveness of phage therapy in nondiabetic mice [19]. This suggests, phage therapy is effective in both immunocompetent and -incompetent mice.…”
Section: Introductionmentioning
confidence: 99%